(untitled) (International Journal of Built Environment and Sustainability, 2024)
According to prolonged project completion times, excessive costs, and inadequate building products, the majority of construction projects are seen as underperforming. Alternatively, stakeholders are encouraged to move from conventional to Industrialized Building Systems (IBS) in line with today’s technology. Previous studies show the performance of IBS practices in the Malaysian construction industry is still at a low level even though the government has diversified promotions and issued instructions for 70% of IBS use in government projects. These selection criteria affect contractors’ performance of IBS practices and need to be done in a systematic way, along with current technology trends and sustainability. Content validity in IBS practice performance is an important step in instrument development. Content validity in IBS practice performance is an important step in instrument development. Therefore, this research aims to evaluate the content validity of the performance effectiveness of IBS practices by using the content validity index (CVI) and modified Kappa sensitivity. In an effort to accomplish the objectives of this study, a questionnaire was created using construct items that were taken from earlier research projects by various researcher. A panel of selected experts who are experienced in the field of IBS, such as CIDB, ​​JKR and contractors have reviewed and evaluated pig instruments to ensure the relevance of each item. The final instrument contains 39 items that are valid and considered permanent and all items will be tested again in the next study. The results showed that the S-CVI/AVE for every item met every requirement and received an outstanding rating for every assessment.